Simple and Green Adipic Acid Synthesis from Cyclohexanone and/or Cyclohexanol Oxidation with Efficient (NH4)xHyMzPMo12O40 (M: Fe, Co, Ni) Catalysts - Sihem Mouanni; Sihem Benadji; Catherine Marchal-Roch; Cherifa Rabia; Tassadit Mazari; Leila Dermeche (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
The oxidation of cyclohexanone and/or cyclohexanol to adipic acid (AA) was performed at 90 °C with a reaction time of 20 h, in the presence of H2O2 as oxidant and transition metal substituted ammonia polyoxometalates of formula, (NH4)xHyMzPMo12O40 (M: Fe, Co, or Ni,  and x = 2.5 or 2.28) as catalysts.  The catalytic results showed that the AA yield is sensitive to the transition metal nature and to the reaction conditions (sample weight and substrate amount). The (NH4)2.29H0.39Co0.16PMo12O40 was found to be the better catalytic system toward AA synthesis from cyclohexanone oxidation, with 40% of AA yield